Antiproliferative Evaluation of Isofuranodiene on Breast and Prostate Cancer Cell Lines. (22nd May 2014) - Buccioni, Michela; Dal Ben, Diego; Lambertucci, Catia; Maggi, Filippo; Papa, Fabrizio; Thomas, Ajiroghene; Santinelli, Claudia; Marucci, Gabriella
Abstract : The anticancer activity of isofuranodiene, extracted from Smyrnium olusatrum, was evaluated in human breast adenocarcinomas MDA-MB 231 and BT 474, and Caucasian prostate adenocarcinoma PC 3 cell lines by MTS assay. MTS assay showed a dose-dependent growth inhibition in the tumor cell lines after isofuranodiene treatment. The best antiproliferative activity of the isofuranodiene was found on PC 3 cells with an IC50 value of 29 μ M, which was slightly less than the inhibition against the two breast adenocarcinoma cell lines with IC50 values of 59 and 55 μ M on MDA-MB 231 and BT 474, respectively. Hoechst 33258 assay was performed in order to study the growth inhibition mechanism in prostate cancer cell line; the results indicate that isofuranodiene induces apoptosis. Overall, the understudy compound has a good anticancer activity especially towards the PC 3. On the contrary, it is less active on Chinese hamster ovary cells (CHO) and human embryonic kidney (HEK 293) appearing as a good candidate as a potential natural anticancer drug with low side effects.